A Case Report of Physical Assault and Traumatic Mechanical Injuries Report to Emergency department of SRMS IMS Bhojipura Bareilly (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
According to section 44 IPC now BNS 2(14) “the word “injury” denotes any harm whatever illegally caused to any person, in body, mind, reputation or property” [1] clinically it is breach of natural continuity of skin or mucous membrane [2] profound study of injuries plays a significant role in medicolegal study. This case report emphasizes the identification of injury types while ruling out alternative injury classification to prevent errors while maintaining accurate medical records.
Keywords: injury; physical assault; BNS